Epistemology of Islamic Law Concerning Human Rights - Y. Sonafist (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Human rights law in the context of answering human rights debate as the spirit of constitutional law, international law, and criminal law. civil law, and procedural law with a blended approach international law and national law. In the Islamic context, the understanding of Human Rights is studied through the understanding of Islamic Law itself. The problems inherent in humans are of interest to scientists, philosophers, and legal experts because humans have inherent will, rights, and freedom. in Islam, all human rights are obligations of a state or individual that cannot be ignored. Hence, human rights in Islamic law are related to the concept of equality which is transcendentally stipulated for the benefit of humans through Islamic law. In Islamic law, humans are beings who have duties and responsibilities and have rights and freedoms based on justice. Human rights are rights that are owned by everyone in accordance with human conditions. Human problems are complex if the rights inherent in humans are not fought for and protected, such as the right to life, the right to freedom, the right to religion, the right to justice, the right to equality, the right to education, the right to freedom of opinion, the right to ownership, and the right to get a job. .In other words, without protection there will be social oppression, human colonization, and authoritarian life arrangements. Therefore, freedom and the will for independence must be protected from oppressive outside forces.